The influence of fasting insulin level in post-gestational diabetes mellitus women receiving low-glycaemic-index diets - Abdul Ghani, Rohana; Shyam, Sangeetha; Arshad, Fatimah; Abdul Wahab, Norasyikin; Chinna, Karuthan; Safii, Nik Shanita; Mohd Yusof, Barakatun Nisak; Kamaruddin, Nor Azmi (Nature Publishing Group, 2014)
Post-gestational diabetes mellitus (GDM) women are recommended weight loss to manage increased cardio-metabolic risks. We investigated the effects of lowering diet glycaemic index (GI) on fasting blood glucose (FBG), serum lipids, body weight and composition of post-GDM women with varying fasting insulin levels (INS). Seventy-seven Asian, non-diabetic women with previous GDM (aged 20-40 years, mean BMI: 26.4±4.6 kgm-2) were recruited. At baseline, 20 subjects with INS <2 μIU ml-1 and 18 with INS ≥2 μIU ml-1 received conventional dietary recommendations (CHDR) only. CHDR emphasised energy and fat intake restriction and encouraged increase in dietary fibre intakes. Twenty-four subjects with INS <2 μIU ml-1 and 15 with INS ≥2 μIU ml-1, in addition to CHDR, received low-GI education (LGI). Changes in FBG, serum lipids, body weight and body composition were evaluated. Subjects with INS <2 μIU ml-1 had similar outcomes with both diets. After 1 year, subjects with INS ≥2 μIU ml-1 who received LGI education had reductions in FBG and triglycerides. Subjects who received CHDR observed increase in both FBG and triglycerides (P<0.05). Among all subjects, diet GI was lower and dietary fibre intakes were higher in LGI compared with CHDR subjects (all P<0.05). Thus, in Asian post-GDM women with normal/higher INS, adding low-GI education to CHDR improved management of FBG and triglycerides. © 2014 Macmillan Publishers Limited All rights reserved.